Not uncommon: HBV genotype G co‐infections among healthy European HBV carriers with genotype A and E infection. (4th May 2021) - Basic, Michael; Kubesch, Alica; Kuhnhenn, Lisa; Görgülü, Esra; Finkelmeier, Fabian; Dietz, Julia; Knabe, Mate; Mücke, Victoria T.; Mücke, Marcus M.; Berger, Annemarie; Zeuzem, Stefan; Sarrazin, Christoph; et al.
Abstract: Background & Aims: HBV genotype G (HBV/G) is mainly found in co‐infections with other HBV genotypes and was identified as an independent risk factor for liver fibrosis. This study aimed to analyse the prevalence of HBV/G co‐infections in healthy European HBV carriers and to characterize the crosstalk of HBV/G with other genotypes. Methods: A total of 560 European HBV carriers were tested via HBV/G‐specific PCR for HBV/G co‐infections. Quasispecies distribution was analysed via deep sequencing, and the clinical phenotype was characterized regarding qHBsAg‐/HBV‐DNA levels and frequent mutations. Replicative capacity and expression of HBsAg/core was studied in hepatoma cells co‐expressing HBV/G with either HBV/A, HBV/D or HBV/E using bicistronic vectors. Results: Although no HBV/G co‐infection was found by routine genotyping PCR, HBV/G was detected by specific PCR in 4%‐8% of patients infected with either HBV/A or HBV/E but only infrequently in other genotypes. In contrast to HBV/E, HBV/G was found as the quasispecies major variant in co‐infections with HBV/A. No differences in the clinical phenotype were observed for HBV/G co‐infections. In vitro RNA and DNA levels were comparable among all genotypes, but expression and release of HBsAg was reduced in co‐expression of HBV/G with HBV/E. In co‐expression with HBV/A and HBV/E expression of HBV/G‐specific core was enhanced while core expression from the corresponding genotype was markedly diminished. Conclusions: HBV/G co‐infections are common in European inactive carriers with HBV/A and HBV/E infection, but sufficient detection depends strongly on the assay. HBV/G regulated core expression might play a critical role for survival of HBV/G in co‐infections.